A new species of Ameroseius (Mesostigmata : Ameroseiidae) from the Indian Thar Desert - Bhattacharyya, Asit K. (Zootaxa, 2004)
Ameroseius dipankari sp. nov. collected from the Indian Thar Desert is described and illustrated in this work. A. dipankari shows affinities with A. eumorphus.